A new multi-purpose 4WD prime mover for oil palm plantation mechanisation. (11th May 2012) - El Pebrian, Darius; Yahya, Azmi
Advancements of oil palm mechanisation in Malaysia were very much constrained by the availability of an appropriate design prime mover to suit the geometric properties of the plantation terrains. Relevant soil mechanical properties of a typical plantation terrain were taken into consideration in the design of a new multi-purpose 4WD prime mover. Proper machine attachments were designed for the prime mover to perform the various identified critical field operations for the oil palm cultivations. The designed power train in the prime mover was found be more than sufficient to traverse the prime mover and operate the machine attachments for the relevant field operations on the worst mineral soil terrain conditions.